Alkane biosynthesis by Aspergillus carbonarius ITEM 5010 through heterologous expression of Synechococcus elongatus acyl-ACP/CoA reductase and aldehyde deformylating oxygenase genes - Sinha, Malavika; Weyda, István; Sørensen, Annette; Bruno, Kenneth S.; Ahring, Birgitte K. (AMB Express, 2017)
In this study we describe the heterologous expression of the recently identified cyanobacterial pathway for long chain alkane biosynthesis, involving the reduction of fatty acyl-ACP to fatty aldehyde and the subsequent conversion of this into alkanes, in the filamentous fungus Aspergillus carbonarius ITEM 5010. Genes originating from Synechococcus elongatus strain PCC7942, encoding acyl-ACP/CoA reductase and aldehyde deformylating oxygenase enzymes, were successfully expressed in A. carbonarius , which lead to the production of pentadecane and heptadecane, alkanes that have not been previously produced by this fungus. Titers of 0.2, 0.5 and 2.7 mg/l pentadecane and 0.8, 1.6 and 10.2 mg/l heptadecane were achieved using glucose, Yeast malt and oatmeal media, respectively. Besides producing alkanes, we found elevated levels of internal free fatty acids and triglycerides in the alkane producing transformant. These findings can indicate that a yet unidentified, native fatty aldehyde dehydrogenase channels back the fatty aldehydes into the fatty acid metabolism, thus competing for substrate with the heterologously expressed fatty aldehyde deformylating oxygenase. These findings will potentially facilitate the future application of robust, fungal cell factories for the production of advanced biofuels from various substrates.